Language Universals and Second Language Acquisition. - Rutherford, William E. (John Benjamins Pub. Co., 1984)
This volume consists of papers presented at the Conference on Language Universals and Second Language Acquisition, University of Southern California, February 1982. Published with the papers are the remarks of the originally assigned discussants. The collection represents an important cross-fertilization between research in grammatical theory and in second language acquisition. Topics dealt with in a number of the papers include word order, markedness, core grammar, accessability hierarchies, and simplified registers. The range of universals discussed embraces phonology, syntax, semantics, and.